Influence of concomitant injuries on post-concussion symptoms after a mild traumatic brain injury – a prospective multicentre cohort study. (29th July 2021) - Ouellet, V; Boucher, V; Beauchamp, F; Neveu, X; Archambault, P; Berthelot, S; Chauny, JM; De Guise, E; Émond, M; Frenette, J; Lang, E; Lee, J; et al.
ABSTRACT: Objectives : To compare post-concussion symptoms (PCS) and return to normal activities between mild Traumatic Brain Injury (mTBI) patients with or without concomitant injuries at 7-and 90 days post-mTBI.Methods : Design: Sub-analysis of a multicentre prospective cohort study. Participants and setting: patients with mTBI from 7 Canadian Emergency Departments. Procedure: Research assistants conducted telephone follow-ups using the Rivermead Postconcussion Symptoms Questionnaire (RPQ) at 7-, 30- and 90 days post-mTBI. Main outcome: Presence of PCS (RPQ: ≥3 symptoms) at 90 days. Secondary outcomes: RPQ score ≥21, prevalence of individual RPQ symptoms and patients' return to normal activities, at 7- and 90-days. Adjusted risk ratios (RR) were calculated.Results : 1725 mTBI patients were included and 1055 (61.1%) had concomitant injuries. Patients with concomitant injuries were at higher risk of having ≥3 symptoms on the RPQ (RR:1.26 [95% CI 1.01–1.58]) at 90 days. They were also at higher risk of experiencing specific symptoms (dizziness, fatigue, headaches and taking longer to think) and of non-return to their normal activities (RR:2.11 [95% CI 1.30–3.45]).Conclusion : Patients with concomitant injuries have slightly more PCS and seemed to be at higher risk of non-return to their normal activities 90 days, compared to patients without concomitant injuries.